Az orvos gyógyító tevékenységének polgári jogi vonatkozásai - Juhász, György (Debreceni Jogi Műhely, 2017)
The article wish to briefly cover the civil liability of the medic. The actuality of this topic is exemplified well by the fact that court trials for compensation of damages against healthcare providers show an increasing tendency year by year. It is deem important to briefly delineate the drawing of line between the civil and criminal liability during the presentation of the civil liability. After speaking about issues of drawing of line, the study is going to cover the effective liability for damages of the medic. While explaining the liability for damages of the medic, it will cover the concept of legal nature of invasive procedures, matters concerning the liability of healthcare institutions, and the basic topics of tort and contractual liability. The article is going to introduce the issues concerning illegality, the patient’s right to self-determination, his or her right to information, the obligation of medics to disclose information, in addition to matters related to the concept of the legal nature of informed consent along with the connected judicial practice in the chapter about the informed consent of the patient. As for closure, during the analysis of issues regarding evidence, it wish to cover the rules of culpability, the choice for healing methods of medics, and medical documentation, respectively.